The IUPHAR Guide to Immunopharmacology: connecting immunology and pharmacology. Issue 1 (2nd March 2020) - Harding, Simon D.; Faccenda, Elena; Southan, Christopher; Pawson, Adam J.; Maffia, Pasquale; Alexander, Stephen P. H.; Davenport, Anthony P.; Fabbro, Doriano; Levi‐Schaffer, Francesca; Spedding, Michael; Davies, Jamie A.
Summary: Given the critical role that the immune system plays in a multitude of diseases, having a clear understanding of the pharmacology of the immune system is crucial to new drug discovery and development. Here we describe the International Union of Basic and Clinical Pharmacology (IUPHAR) Guide to Immunopharmacology (GtoImmuPdb), which connects expert‐curated pharmacology with key immunological concepts and aims to put pharmacological data into the hands of immunologists. In the pursuit of new therapeutics, pharmacological databases are a vital resource to researchers through providing accurate information on the fundamental science underlying drug action. This extension to the existing IUPHAR/British Pharmacological Society Guide to Pharmacology supports research into the development of drugs targeted at modulating immune, inflammatory or infectious components of disease. To provide a deeper context for how the resource can support research we show data in GtoImmuPdb relating to a case study on the targeting of vascular inflammation. Abstract : The International Union of Basic and Clinical Pharmacology (IUPHAR) Guide to Immunopharmacology (GtoImmuPdb) connects expert‐curated pharmacology with key immunological concepts and aims to put pharmacological data into the hands of immunologists. Pharmacological databases are a vital resource to researchers through providing accurate information on the fundamental science underlying drug action. This extension to the existing IUPHAR/BPS Guide to Pharmacology supports research into the development of drugs targeted at modulating immune, inflammatory or infectious components of disease.